Analisis Kemampuan Self-Control Pada Peserta Didik Di Sekolah Dasar - Qomariah, Annisa; Arifin, Nurdin; Oktaviani, Siska; Amaliah Dewi, Vivin (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
The phenomenon that occurs in class VI elementary school is that learning discipline is still low, easily provoked by emotions, easily distracted, and attitudes among students that respect low achievement. This problem is related to the ability to control oneself. This research aims to analyze students' self-control abilities descriptively with the subject of class VI students. The sampling technique uses purposive sampling technique and data collection uses observation, documentation and interview techniques to be able to explore and uncover problems. Researchers tested the validity of the data using source triangulation techniques. The results of this study show that participants' self-control abilities were studied from the aspects of good behavioral control, poor cognitive control, and very good decision control. In this research, external factors from the family and environment dominate the self-control abilities of elementary school students.